The solution of the set of equations 3x-2y=3 and 2x+3y=2 has to be determined.

3x-2y=3 ...(1)

2x+3y=2 ...(2)

3*(1) - 2*(2)

=> 9x - 6y - 4x - 6y = 9 - 4

=> 5x = 5

=> x = 1

Substituting x = 1 in (1)

3 - 2y...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

The solution of the set of equations 3x-2y=3 and 2x+3y=2 has to be determined.

3x-2y=3 ...(1)

2x+3y=2 ...(2)

3*(1) - 2*(2)

=> 9x - 6y - 4x - 6y = 9 - 4

=> 5x = 5

=> x = 1

Substituting x = 1 in (1)

3 - 2y = 3

=> y = 0

The solution of the set of equations is (1, 0).

**The correct answer is option A.**